Sinergi Hepta Helix untuk Edukasi Perubahan Iklim Berbasis Komunitas di Cirebon - Sopidi Sopidi; Wahyono Wahyono (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
Cirebon faces severe ecological vulnerability due to the impacts of coal-fired power plants and coastal abrasion, exacerbated by the community’s low level of mitigation literacy (28%). Sectoral responses thus far have been ineffective in strengthening local resilience. This community-engaged research aims to implement the Hepta Helix collaboration model to build a participatory climate education ecosystem. Employing Participatory Action Research (PAR) with an Asset-Based Community Development (ABCD) approach, the study involves seven key cross-sector actors.The findings indicate a significant shift in social paradigm—from a confrontational deficit mentality to a collaborative asset-based mindset. This synergy successfully orchestrated the roles of each actor and generated concrete innovations such as the institutionalization of the Environmental Verse Tafsir, youth-led digital campaigns, and community-based biopore revitalization. The study concludes that the Hepta Helix collaboration effectively breaks down sectoral ego barriers and strengthens community adaptation capacity at the grassroots level in a sustainable manner.